2016
DOI: 10.1097/hjh.0000000000000898
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic parameters in hypertensive diabetic patients

Abstract: Aortic stiffness and PP amplification were not interrelated, suggesting that these markers may provide complementary information for cardiovascular risk. New therapeutic strategies targeting pressure pulsatility should take into account the impact of hyperglycemia and increased heart rate in diabetic hypertensives. Gender influence on the role of autonomic nervous system in attenuating pressure wave reflections remains to be further established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…According to previous studies, we have determined a PWV index based on a theoretical PWV calculated through a linear regression on major factors correlated with aortic stiffness, such as age, gender, mean BP, and HR …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to previous studies, we have determined a PWV index based on a theoretical PWV calculated through a linear regression on major factors correlated with aortic stiffness, such as age, gender, mean BP, and HR …”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the different risk factors associated with PWV index . In our study, we constructed a decision tree model, based on data from a cross‐sectional study to investigate the different factors associated with PWV index (positive or negative values).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HRV is one of the first symptoms of cardiac autonomic neuropathy in diabetes, which is also associated with blood pressure dysregulation and left ventricular hypertrophy [2]. Furthermore, recent studies have also shown increased PPA in type 2 diabetic hypertensive patients [3], suggesting vascular remodeling due to increased arterial stiffness as another possible etiology of HRV. It would be interesting to analyze the influence of obesity on HRV and PPA in diabetic patients.…”
mentioning
confidence: 99%